Market power and tax aggressiveness - Gomes, Jose Valdir Marcolino (2022)
The aim of this study is to analyze whether Brazilian companies listed on the Brasil, Bolsa and Balcão (B3) with greater market power are more tax aggressive. The gap in this research arose from the absence of empirical evidence on the relations between the market power of companies and their tax aggressiveness, when operating in a developing market, and in a country with a code law legal structure. This paper contributes to filling this gap by studying this relation through multiple linear regression and quantile regression analysis. The results indicate that, in Brazil, the greater the company's market power, the more aggressive its tax planning is, when comparted to the industry median.